Pengaruh Total Quality Management (Tgm, Gaya Kepemimpinan,. Kedisiplinan Kerja dan Fungsi Monitoring) Terhadap Kinerja Karyawan - Heriyanto Heriyanto (Prodi Ilmu Administrasi Negara, 2018)
Influence Total of Quality Management (TQM), Style Leadership, JobDiscipline and Function of Mentoring to Performance Employees of PT.Kemakmurn Berkah Timber Samarinda.To be able improved Performance Employees in a company ororganization, hence required by factors able to improve Performance itself.As for the factors is Totalizeing Quality Management, Style Leadership, JobDiscipline and Function of Mentoring.This Formula research internal issue is